Cyclodextrin-based miniaturized solid phase extraction for biopesticides analysis in water and vegetable juices samples analyzed by ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. (1st July 2017) - Peng, Li-Qing; Ye, Li-Hong; Cao, Jun; Chang, Yan-xu; Li, Qin; An, Mingrui; Tan, Zhijing; Xu, Jing-Jing
Highlights: A cyclodextrin based miniaturized solid-phase extraction was developed. The proposed method involves the use of UHPLC-Q-TOF/MS. The innovative method was efficient and economic for biopesticides extraction. This method was applied for the determination of biopesticides in water and vegetable juices. Abstract: A cyclodextrin-based miniaturized solid-phase extraction was developed to extract biopesticides from water and vegetable juices. The analytes were detected by ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry. In the solid-phase extraction (SPE) procedure, the liquid sample solution is passed through a packed column filled with 40 mg of HP-β-CD, and then the target analytes are absorbed and finally eluted with methanol-acetic acid (90:10, v/v) into a collection tube. The limits of quantification ranged from 3.73 to 16.51 ng/mL for a water matrix, from 2.62 to 13.23 ng/mL for an orange juice matrix and from 1.76 to 10.35 ng/mL for a tomato juice matrix, respectively. The average recovery values were in the range of 88.3–95.9% for the spiked samples. The established methodology was successfully applied to analyze sanguinarine, berberine, rotenone and osthole in water, orange juice and tomato juice.